Effect of Stepped Care on Sexual Interest and Enjoyment in Distressed Patients with Head and Neck Cancer: A Randomized Controlled Trial - Laura E.R. Schutte, MSc; Heleen C. Melissant, PhD; Femke Jansen, PhD; Birgit I. Lissenberg-Witte, PhD; C. René Leemans, MD, PhD; Mirjam A.G. Sprangers, PhD; Marije R. Vergeer, MD; Irma M. Verdonck-de Leeuw, PhD; Ellen T.M. Laan, PhD (Sexual Medicine, 2021)
Introduction: A recent randomized controlled trial (RCT) in patients with head and neck cancer (HNC) with psychological distress showed that a stepped care (SC) program targeting psychological distress compared with care as usual (CAU), is (cost)effective in reducing psychological distress. Aim: The aim of the present study was to investigate whether SC can coalleviate problems with sexual interest and enjoyment. A secondary aim was to investigate whether the presence of an unmet sexual health need and having a psychiatric disorder (depression or anxiety) at baseline moderated any effect of SC on these sexual variables until 1-year follow-up. Methods: HNC survivors (N = 134), randomized to SC or CAU, were assessed regarding their sexual interest and enjoyment before and after the intervention and at 3, 6, 9, and 12 months follow-up. Linear mixed models were used to evaluate differences in the course of sexual interest and enjoyment between SC and CAU. Main Outcome Measure: The “sexuality” symptom subscale, part of the European Organization for Research and Treatment of Cancer, Quality of Life Questionnaire, Head and Neck Cancer–specific module. Results: Of all patients, 76.1% had an unmet sexual need at baseline, 24.6% had a psychiatric disorder (anxiety or depression). SC did not reduce problems with sexual interest and enjoyment at any of the follow-up measurements compared with CAU (P = .85). This was neither moderated by an unmet sexual health need at baseline (P = .64) nor by the presence of a psychiatric disorder at baseline (P = .59). Conclusion: A substantial number of patients with HNC have unmet sexual health needs. SC targeting psychological distress does not reduce problems with sexuality in these patients. Interventions specifically targeting sexuality are recommended.Schutte LER, Melissant HC, Jansen F, et al. Effect of Stepped Care on Sexual Interest and Enjoyment in Distressed Patients with Head and Neck Cancer: A Randomized Controlled Trial. Sex Med 2021;9:100304.